THE FIRST FIND OF GEOLABIDIDAE (SORICOMORPHA, MAMMALIA) IN ASIA (UPPER PALEOCENE OF MONGOLIA) - Lopatin A.V. (My University, 2004)
Gobigeolabis verigranum gen. et sp. nov. is described based on jaw fragments from the Upper Paleocene Zhigden Member of the Naran Bulak Formation of the Tsagan-Khushu locality (Mongolia). This is the first Asian member of the Geolabididae, a soricomorph family that has previously been recorded from the Upper Cretaceous-Lower Miocene of North America. G. verigranum was an extremely small mammal; the dimensions of its m1 suggest this animal was approximately 2.25 g in body weight (i.e., similar in size to the smallest extant shrews).
Keywords: Geolabididae; Soricomorpha; body weight of extinct mammals; Late Paleocene; Mongolia; Cenozoic::Paleogene::Paleocene; Кайнозой::Палеоген::Палеоцен